Alternate Phenotype-Genotype Selection Method for Developing Photoperiod Insensitive, Good Cooking Quality and Potential High Yielding Rice Lines - Sreewongchai, Tanee; Rattanapol , Parichut; Vichukit, Vichan (Agriculture and Natural Resources, 2014)
The Khao Dawk Mali 105 (KDML105) rice variety is photosensitive but considered to be good quality rice in Thailand. Crossing between KDML105 and a new plant type variety Qiqnizhan (Chinese origin), was performed to select photoperiod-insensitive, good cooking quality and high yielding lines. Switching between phenotype and genotype selections was made based on target traits. Selection for photoperiod insensitivity was made in the F2 population grown under long day conditions with a DNA marker linked to the fgr and Wx genes. The F3 population confirmed the recombinants with desirable ideotypes having photoperiod insensitivity and good cooking quality. Moreover, six lines were selected in the F4 generation with more fragrant grain, lower amylose content and higher yield than those of their parents and standard varieties. The informative genetic markers linked to target traits were utilized which accelerated the breeding program.